Case reportReed’s syndrome: case report and review of literature - Meszyńska, Elżbieta; Bergler-Czop, Beata; Brzezińska-Wcisło, Ligia (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2012)
Leiomyomas are benign tumors that develop from smooth muscle cells. Coexistence of the rare skin manifestations together with uterine leiomyomas is known as the Reed’s syndrome (multiple cutaneous and uterine leiomyomatosis – MCUL). The suspicion of Reed’s syndrome, which is based on the morphology of the skin lesions (multiple, small, oval, reddish-brown tumors around hair follicle, mostly painful) should be confirmed by the histopathological examination. All patients with cutaneous leiomyomatosis should undergo prophylactic examinations to exclude renal cell cancer. Treatment is limited and based on surgical excision of the lesion, carbon dioxide laser ablation or cryosurgery. We have reported a case of Reed’s syndrome with typical occurrence of skin changes, uterine leiomyomas and renal cysts. Regular checkup is required in this group of patients because of the higher risk of development of malignant changes.